2018
DOI: 10.31235/osf.io/jw8am
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconciling Religion and LGBT Rights: Christian Universities, Theological Orientations, and LGBT Inclusion

Abstract: Why do some Christian colleges and universities approve LGBT groups and nondiscrimination policies while others resist them? Scholars are beginning to develop models to explain LGBT inclusion in schools, but they have undertheorized the role of religion in facilitating or impeding LGBT inclusion. In this article, I draw from literature on religion and the "culture wars," especially insights on religions' theological orientations, to explain Christian colleges and universities' inclusion of LGBT students. Ishow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 9 publications
2
25
2
Order By: Relevance
“…We also assessed whether schools with a higher share of women students would be more likely to have LGBTQ student groups since women are slightly more likely to personally identify as LGBTQ, are significantly more likely to support LGBTQ rights, and are more willing to join LGBTQ groups even as straight allies. We similarly found support for this expectation (hypothesis 5), and this finding contrasts with those of past studies that found the percentage of women at a school to be insignificantly or weakly related to LGBTQ student center presence (Coley 2017;Kane 2013). Additionally, for our measure of organizational resources, we considered whether schools that are home to Democratic student organizations might be more likely to be home to LGBTQ student groups, since members of such organizations may contain many supporters of LGBTQ rights who would be willing to join and/or lend their support for LGBTQ groups.…”
Section: Discussioncontrasting
confidence: 97%
“…We also assessed whether schools with a higher share of women students would be more likely to have LGBTQ student groups since women are slightly more likely to personally identify as LGBTQ, are significantly more likely to support LGBTQ rights, and are more willing to join LGBTQ groups even as straight allies. We similarly found support for this expectation (hypothesis 5), and this finding contrasts with those of past studies that found the percentage of women at a school to be insignificantly or weakly related to LGBTQ student center presence (Coley 2017;Kane 2013). Additionally, for our measure of organizational resources, we considered whether schools that are home to Democratic student organizations might be more likely to be home to LGBTQ student groups, since members of such organizations may contain many supporters of LGBTQ rights who would be willing to join and/or lend their support for LGBTQ groups.…”
Section: Discussioncontrasting
confidence: 97%
“…The role of religion in sexual minorities’ wellbeing is still not clear, with studies reporting it as a positive resource in the lives of many LGBQ+ individuals ( Rosenkrantz et al, 2016 ), while others indicating it as a risk factor for experiencing ISS ( Lingiardi et al, 2012 ; Severson et al, 2014 ; Sowe et al, 2014 ; Nardelli et al, 2020 ). This lack of coherence in literature may depend on the fact that not all religious contexts are stigmatizing ( Coley, 2017 ), and that some LGBQ+ people succeeded in reconciling their faith with their sexual identity ( Beagan and Hattie, 2015 ). In Italy, where the present research was conducted, the most practiced religion is Catholicism, and there is a lack of openly inclusive LGBQ+ contexts.…”
Section: Introductionmentioning
confidence: 99%
“…135‐136). Even pro forma statements of support by politicians can shape people’s sense of “what is possible” (Johnston 2011, p. 28), inspiring people to form new organizations or participate in existing organizations that do not directly target the state, yet seem acceptable or even popular in a given political environment (see similar arguments by Coley 2017; Fine 2012; van Dyke et al 2007). We suggest that two key indicators of political opportunities may be particularly helpful for understanding the presence of shooting sports organizations: the partisan leaning of a state and the existence of pro‐gun legislation in a state.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although there are various ways to measure Republican Party strength in a state, we follow other scholars of student organizations (e.g., Coley 2017; Fine 2012) by employing a measure of a state’s support for the Republican Party candidate in the most recent Presidential election—in this case, a state’s support for Donald Trump in the 2016 Presidential election. Although a state’s support for Trump in 2016 serves as a general proxy for a state’s pro‐Republican leanings, it is a particularly helpful proxy for our case, since Trump was running for President during the very time period that NRA, NSSF, SSSF, MidwayUSA, and USA College Clay Target League were making their renewed push to promote shooting sports organizations at U.S. colleges and universities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation